Sustainability index development for manufacturing industry. (December 2017) - Latif, Hasan H.; Gopalakrishnan, Bhaskaran; Nimbarte, Ashish; Currie, Kenneth
Abstract: Manufacturing industries are adopting new techniques and philosophies to address the acute shortage of non-renewable energy. Many of these manufacturing industries are focusing on achieving sustainability in every possible stage of their production, from raw material to the recycling of waste. Thus, the significance of using renewable energy, properly handling waste, and progressively conserving the environment is increasing day by day. In this research, the definition of sustainability is quite specific: being productive while making little to no impact on non-replenishable resources. The objective of the research is to determine the sustainability index of manufacturing plants. Since the topic has a broad scope, this research is limited to small and medium scale industries, which have common sets of operation and defined process plans. Besides, the focus is on non-hazardous waste and the indicators of the index are selected with respect to energy efficiency, workers' health and safety and waste reduction potential. An interactive model has been developed to determine the sustainability index based on user responses. Based on the sustainable index, the model is able to provide suggestions to improve sustainability as well as carbon footprint reduction. The research has used datasets from various projects of the Industrial Assessment Center (IAC) at West Virginia University to build the knowledge database. The interactive model is validated by case studies from the IAC. The outcome of this research is a model that can assist industry to identify their shortcomings in achieving sustainability, determine the carbon footprint reduction potential, and compare the sustainability index as a benchmark measure.